STUDI LOKASI PUSAT PEMERINTAHAN KABUPATEN DHARMASRAYA - Sari, Zesa Mulyanda; Juwita, Erna; Zuriyani, Elvi (Pendidikan Geografi, 2013)
Problems in this area is the complaints and the perception of the public about the central government and local services are too far away from where people live well to take care of the administrative requirements such as taking care of Birth Certificate, Family Card (KK), and other purposes, the central government since the distance is too far .This research study aims to determine the location of County Government Center Dharmasraya, this research is descriptive. Population in this research is the head of a family that is in Nagari Koto Baru, Dharmasraya, totaling 3,327 households (samples taken with proportional random sampling technique to the proportion of 5% so that the sample amounted to 164 households.The research found that: 1) Distance Nagari Koto Baru with the central government in Dharmasraya about 35 km. Based on the average rating of the 164 respondents, looks very much about (87.5%), travel time (70%) responded Â± 2 hours more / longer, while the costs (55%) say the economic impact on society of the cost of the society should be removed. 2) Infrastructure facilities and infrastructure Nagari Koto Baru with the central government in Dharmasraya average score was 2.94 with a performance level of 74.6% of respondents who are in pretty good criteria. This shows that the infrastructure in Dharmasraya good views of the availability of facilities and infrastructure. 3) Impact of the district administrative center away from residential communities in Nagari Koto Baru is very influential on the distance, time and expenses to be incurred. Whereas in view of the infrastructure facilities and infrastructure in Nagari Koto Baru less influence on this area.